Comparative study of novel tubular flux-reversal transverse flux permanent magnet linear machine - Zhu, Shaohong; Cox, Tom; Gerada, Chris (2017)
This paper presents a novel tubular flux-reversal transverse flux permanent magnet linear machine (FR-TFPMLM), in which both magnet and armature winding are located at the short primary side whereas the secondary side is composed of only magnetic steel. This configuration is typically used in long stroke applications to save magnet material. With different configurations of phase winding, the machine can have two topologies, viz. axial three-phase and circumferential three-phase. The structure and operational principle of both topologies are firstly introduced; And then both theoretical and numerical analyses are performed. The electromagnetic characteristics of both machines, with particular focus on thrust force and force ripple, are optimized. Finally, the performances of optimal schemes of these two topologies are summarized and compared.